أثر استخدام تطبيق أندرويد لينج في ميول الطلاب إلى تعلم اللغة العربية (دراسة تجريبية في مدرسة المرشدية المتوسطة الإسلامية) - Nurwulaningsih; Mawani; El Zahraa, Fatimah (Penerbit Minhaj Pustaka, 2025)
This study focuses on the effect of using the Ling android application on students' interest in learning Arabic in seventh grade students at MTs Al Mursyidiyyah Pamulang. This study aims to measure the level of student interest and determine the specific effect of using the Ling application on students' interest in learning Arabic. The method used in this study is a quasi-experimental method with a nonequivalent control group design. The subjects of the study consisted of two classes, namely the experimental class that used the Ling application and the control class that did not use it. Data were collected through a learning interest questionnaire that included feelings of pleasure and interest, attention, awareness, and focus. The results showed that the average post-test score in the experimental class was 88.26 while the average post-test score in the control class was 77.61. The data analysis technique using the independent sample t-test showed sig. (2-tailed) 0.000 which means there is a significant difference between the experimental class and the control class. Thus, it can be concluded that the use of the Ling application has a positive effect on students' interest in learning Arabic.